New records and combinations for Neotropical Leptophlebiidae (Ephemeroptera) - Peters, J. G.; Flowers, R. W.; Hubbard, M. D.; Dominguez, E.; Savage, H. M. (Zootaxa, 2005)
Several species of Leptophlebiidae (Atalophlebiinae) from South and Central America are given new generic combinations based on improved knowledge of the Leptophlebiidae of the region. These are: Tikuna bilineata (Needham & Murphy, 1924, Choroterpes) comb. n.; Terpides vinculum (Traver, 1947, Choroterpes) comb. n.; Hermanella costalis (Navás, 1934, Thraulus) comb. n.; Ulmeritoides haarupi (Esben-Petersen, 1912, Thraulus) comb. n. (synonyms Deleatidium vittatum, Thew, 1960 syn. n. and Ulmeritoides fidalgoi Domínguez, 1995 syn. n.). In addition, we give new distribution records for Tikuna bilineata, report Choroterpes from Colombia, and describe Hagenulus marshalli sp. n. from Ecuador based on two male imagos. Hagenulus marshalli sp. n can be distinguished from other members of the genus by the asymmetrical fork of MP (small cross vein present) and the short, slightly twisted penes without apical spines. These are the first confirmed records for Choroterpes, Tikuna and Hagenulus from continental South America, extending Hagenulus from the Greater Antilles into Ecuador, Choroterpes from Central America into Colombia, and Tikuna from Costa Rica into Brazil, Colombia, Ecuador, Surinam and Venezuela.